Christians in Active Politics : The 'Why and How' of Christians' Active Participation in the Secular Political Affairs - Fletcher, Christopher D. M. (Book collections on Project MUSE., 2007)
This 3rd edition incorporates all of the latest ancillary diagnostic and prognostic techniques for effective evaluation and confident interpretation of suspected tumor specimens. Plus, more than 50 internationally recognized authorities and over 3,100 full-color illustrations provide an up-to-date account of tumor morphology, the application of modern diagnostic techniques (including molecular genetics), and key aspects of differential diagnosis.